2014
DOI: 10.4028/www.scientific.net/msf.793.143
|View full text |Cite
|
Sign up to set email alerts
|

Phase Evaluation and its Hydrogen Correlation of the FeAl<sub>3</sub> and FeAl<sub>2</sub> Intermetallic Alloys during Mechanical Ball-Milling with Water

Abstract: FeAl3 and FeAl2 intermetallic alloys composition was produced by conventional casting technique. Typically these intermetallic alloys are susceptible to hydrogen environment embrittlement. In this process, water vapor in the air induced cleavage fracture of intermetallic alloys. In order to take advantage of this phenomenon, we evaluate the embrittlement reaction during ball-milling of the pre-alloyed intermetallic material and water under different milling times. During the corrosion reaction, the amount of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The reaction between water vapor and aluminum also generates hydrogen (Salazar et al 2016 , 2005 ). Others authors have proposed hydrogen production using iron aluminides (López-Miranda and Rosas 2019 ; Romero-Romero et al 2014 ; García de León et al 2013 ). This suggests that this method could be used to produce hydrogen; however, it requires more studies.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction between water vapor and aluminum also generates hydrogen (Salazar et al 2016 , 2005 ). Others authors have proposed hydrogen production using iron aluminides (López-Miranda and Rosas 2019 ; Romero-Romero et al 2014 ; García de León et al 2013 ). This suggests that this method could be used to produce hydrogen; however, it requires more studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, while some studies report the formation of a mixed crystalline and amorphous structure as observed at the end of the 2 θ positions, others claim that the weld zone and HAZ produced are fully crystalline [16]. Apart from Aluminium matrix, the peaks also correspond to the peaks of Al 4 Cu 9 [17], Al 4 Li 9 [18], Al 2 CuMg [19], FeAl 2 [20], Al 2 Cu [21], Al 8.9 Li 1.1 [22], AlLi [23] and Mg 2 Si [24,25], suggesting their possible presence in the weldment. This confirms that the formation of multiple phases does not affect the weld zone strength.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction between water vapor and aluminum also generates hydrogen (Salazar et al 2016;Salazar, Pérez & Rosas, 2005). Other authors have proposed hydrogen production using iron aluminides (López-Miranda et al 2019;Romero-Romero et al 2014;García de León et al 2013). This suggests that this method could be used to produce hydrogen, which requires more studies.…”
Section: Other Benefits From the New Processmentioning
confidence: 99%